Studi Literatur: Efektivitas Intervensi Isometric Handgrip Exercise Untuk Menurunkan Tekanan Darah Pada Lansia Dengan Hipertensi - Nur Melizza; Ilvi Maulidiana Putri (Indonesian Health Science Journal, 2022)
Introduction: The elderly are a group that is susceptible to various health problems, especially in the cardiovascular system such as hypertension. Hypertension often occurs in the elderly because of a decrease in organ function and structure. One of the non-pharmacological interventions that can be given is isometric handgrip exercise. This study aims to examine the effectiveness of isometric handgrip exercise to reduce blood pressure in the elderly with hypertension. Methods: This study uses the literature review method by analyzing scientific articles from 2017 to 2021. The data obtained are 10 journals from Science Direct, Pubmed, Google Scholar, ProQuest, and SAGE databases. Journal quality was assessed using Critical An appraisal from the Joanna Briggs Institute and analyzed using thematic analysis. Results: The results of 10 journals that have been analyzed, the tool used for isometric handgrip exercise using a dynamometer with muscle strength intensity 30%-90% MVC with a duration of 8-12 weeks can reduce high blood pressure in the elderly with hypertension. Conclusion: In this study, it was found that a dynamometer that uses maximal voluntary contraction (MVC) with an intensity of 30%-90% can have a positive effect in lowering blood pressure in the elderly with hypertension.